Implementation of Green Service Innovation at Food & Beverage Department Beach Resort & Spa - Putra, I Ketut Adi Bagaskara; Sari, I Gusti Agung Mas Krisna Komala; Mataram, I Gusti Agung Bagus (Journal of Business on Hospitality and Tourism, 2022)
Food & beverage department service has a very important role in a hotel, because the good and bad of the service will affect the level of popularity of the hotel. During the delivery of excellent quality service will create high value, which can create customer satisfaction. The purpose of this study is to analyses the application of green service innovation and what obstacles are faced in the application of green service innovation at Azul beach club Bali Mandira Beach Resort & Spa. This study uses a qualitative descriptive analysis method by dividing three stages, namely reducing data, presenting data and then drawing conclusions. The data collection methods in this study are observation, interviews, literature studies and documentation. The results of this study show that of the 9 (nine) indicators of green service innovation applied to the F&B department at Azul beach club applied 100% well. The obstacles faced in the implementation of green service innovation are maintaining consistency and commitment, product resilience, spending funds and also limited product raw materials.